2021
DOI: 10.3389/fphar.2020.593514
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Retinal Structure and Ultrastructure in the Aged Mice Correlate With Differences in the Expression of Selected Retinal miRNAs

Abstract: Age and gender are two important factors that may influence the function and structure of the retina and its susceptibility to retinal diseases. The aim of this study was to delineate the influence that biological sex and age exert on the retinal structural and ultrastructural changes in mice and to identify the age-related miRNA dysregulation profiles in the retina by gender. Experiments were undertaken on male and female Balb/c aged 24 months (approximately 75–85 years in humans) compared to the control (3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 98 publications
2
14
1
Order By: Relevance
“…The circRNA showing the most significant change between male and female mice was mmu_circ_0004351, with a fold change of 17.5 and an FDR adjusted Wilcoxon Mann-Whitney P -value of 4.6 × 10 –32 (Figure 4C ). miRNAs for which only 5% of the observed variance could be attributed to the mouse sex, were also partially differentially expressed, and have been previously reported in literature for single tissues or other species, such as mmu-miR-27a-3p and miR-27b-3p ( 44 , 45 ) and miR-16-5p and miR-21-3p ( 46 ).…”
Section: Resultssupporting
confidence: 65%
“…The circRNA showing the most significant change between male and female mice was mmu_circ_0004351, with a fold change of 17.5 and an FDR adjusted Wilcoxon Mann-Whitney P -value of 4.6 × 10 –32 (Figure 4C ). miRNAs for which only 5% of the observed variance could be attributed to the mouse sex, were also partially differentially expressed, and have been previously reported in literature for single tissues or other species, such as mmu-miR-27a-3p and miR-27b-3p ( 44 , 45 ) and miR-16-5p and miR-21-3p ( 46 ).…”
Section: Resultssupporting
confidence: 65%
“…Some of these miRNAs have been identified previously in association with AMD, with miR-26a-5p and miR-27a-3p showing directional changes consistent with the literature (Grassmann et al, 2014;Szemraj et al, 2015) and let-7d-5p and miR-574-3p showing a directional change opposite to that reported in the literature (Ertekin et al, 2014;ElShelmani et al, 2020). Additionally, miR-27a-3p is a mediator of the inflammatory response (Zhang et al, 2018), and its overexpression was associated with increased oxidative stress and retinal damage (Ren et al, 2021), and increasing in aging mouse retinas (Hermenean et al, 2021). Interestingly, here we show that modulation in miR-26a-5p and miR-27a-3p correlated with histological features, specifically TUNEL + cell count and retinal volume, respectively.…”
Section: Clinical Serum Mirna Profiles Demonstrate Consistencies With...supporting
confidence: 78%
“…Several age-dependent cellular and molecular changes have been described in mouse retinas, such as, photoreceptor mislocalization (Sugita et al, 2020 ) and vascular and RPE changes (Hermenean et al, 2021 ). Regarding metrics captured by OCT, although some studies have found age-dependent alterations in mouse retinas, such as auto-fluorescence (Ferdous et al, 2021 ) and scattering diversity (Gardner et al, 2020 ), these cannot be directly compared with our results.…”
Section: Discussionmentioning
confidence: 99%